Polyurethane composite material applied to new energy automobile accessory component
By using specific formula polyurethane composite materials in new energy vehicle accessories components, the problem that traditional materials are difficult to meet the needs of new energy vehicles in terms of strength, toughness and weather resistance is solved, and high-performance polyurethane composite materials are achieved.
Patent Information
- Application Number
- CN202411841564.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional materials are difficult to meet special needs such as strength, toughness and weather resistance in new energy vehicle accessories components.
A polyurethane composite material is used in the formulation of polytetrahydrofuran ether glycol, polybutyl adipate glycol, diphenylmethane diisocyanate, toluene diisocyanate, 1,4-butanediol, ethylene glycol, nanosilica, antioxidants and ultraviolet absorbers to form the composite material through a specific preparation process.
The polyurethane composite material has excellent performance in hardness, flexibility, heat resistance and UV resistance, and can meet the high-performance needs of new energy vehicle accessories components such as battery housings and bumpers.
Smart Images

Figure BDA0005188085200000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material preparation, and in particular to a polyurethane composite material applied to new energy automobile accessory components. Background Art
[0002] With the rapid development of the new energy vehicle industry, the performance requirements for automotive parts and components are increasing. Traditional materials are difficult to fully meet the special needs of new energy vehicles in terms of strength, toughness, weather resistance, etc. As a high-performance material, polyurethane composites play an important role in new energy vehicle parts and components. Polyurethane composites not only have a much lower density than traditional metal materials, but also have excellent strength. At the same time, polyurethane composites have strong corrosion resistance and can effectively resist erosion in humid, acidic and alkaline environments. It shows good flexibility during the molding process and can be prepared into various complex shapes of parts through molding, injection molding, etc.
[0003] Therefore, a composition that can meet the special requirements of new energy vehicles in terms of strength, toughness, weather resistance, etc. is needed to improve the deficiencies of the existing technology. Summary of the invention
[0004] The main purpose of the present invention is to provide a polyurethane composite material used in new energy automobile parts and a preparation method thereof, which can effectively solve the problems in the background technology.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A polyurethane composite material used for new energy automobile parts components. The composition comprises, by weight: 30-60 parts of polytetramethylene glycol, 10-30 parts of polybutylene adipate glycol, 15-35 parts of diphenylmethane diisocyanate, 5-15 parts of toluene diisocyanate, 3-8 parts of 1,4-butanediol, 2-6 parts of ethylene glycol, 1-5 parts of nano silicon dioxide, 0.5-2 parts of antioxidant, and 0.3-1.5 parts of ultraviolet absorber.
[0007] Preferably, the polyurethane composite material used for new energy vehicle parts components includes, by weight: 40-50 parts of polytetramethylene ether glycol, 15-25 parts of polybutylene adipate glycol, 20-30 parts of diphenylmethane diisocyanate, 7-13 parts of toluene diisocyanate, 4-7 parts of 1,4-butanediol, 3-5 parts of ethylene glycol, 2-4 parts of nano-silica, 1-1.5 parts of antioxidant, and 0.8-1.2 parts of ultraviolet absorber.
[0008] Preferably, the polyurethane composite material used for new energy vehicle parts components includes, by weight: 50 parts of polytetramethylene ether glycol, 25 parts of polybutylene adipate glycol, 28 parts of diphenylmethane diisocyanate, 12 parts of toluene diisocyanate, 6 parts of 1,4-butanediol, 5 parts of ethylene glycol, 4 parts of nano-silica, 1.5 parts of antioxidant, and 1 part of ultraviolet absorber.
[0009] Preferably, the molecular weight of the polytetramethylene ether diol is 3000-4000, and the molecular weight of the polybutylene adipate diol is 1500-2500.
[0010] Preferably, the particle size of the nano-silicon dioxide is 10-50 nm.
[0011] A method for preparing the polyurethane composite material used in new energy vehicle parts components, the specific steps are as follows:
[0012] Step 1: Raw material pretreatment: polytetrahydrofuran ether glycol, polybutylene adipate glycol, 1,4-butanediol, ethylene glycol and antioxidant are vacuum dehydrated for 2-4 hours, and nano-silica is dried for 2-3 hours;
[0013] Step 2: Prepolymer synthesis: under nitrogen protection, add dehydrated polytetramethylene glycol, polybutylene adipate glycol, diphenylmethane diisocyanate and toluene diisocyanate into a reaction kettle, control the temperature at 50-70°C, and stir the reaction for 1-2h;
[0014] Step 3: Chain extension reaction: Add 1,4-butanediol 5, ethylene glycol and UV absorber to the prepolymer, continue stirring and heat to 70-90°C, and react for 2-3h;
[0015] Step 4: Filler dispersion: Slowly add the dried nano-silica into the reaction system and disperse it for 30-60 minutes under high-speed stirring (800-1200 rpm);
[0016] Step 5: Molding treatment: Pour the reacted composite material into a mold, cure it at 100-120°C for 2-4 hours, and then place it at room temperature for 24-48 hours.
[0017] Preferably, in step 1, the vacuum dehydration temperature is 85-95°C, and the drying temperature of nano-silicon dioxide is 130-140°C.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The polyurethane composite material of the present invention has moderate hardness, can meet the requirements of new energy automobile parts and components at different positions, and also has good flexibility. Similarly, the embodiment material to which an antioxidant and an ultraviolet absorber are added and the raw material ratio is reasonable has good performance in heat resistance (tensile strength retention rate) and ultraviolet resistance (tensile strength retention rate). All performance indicators can well meet the use requirements of new energy automobile parts and components such as battery housings, bumpers, etc., and has excellent performance in strength, toughness, weather resistance, etc., and has obvious advantages in these aspects compared with traditional materials. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] Example 1
[0022] Step 1: Raw material pretreatment: 45 parts of polytetrahydrofuran ether glycol (molecular weight of 3500), 20 parts of polybutylene adipate glycol (molecular weight of 2000), 5 parts of 1,4-butanediol, 4 parts of ethylene glycol and 1.2 parts of antioxidant were dehydrated at a vacuum temperature of 90°C for 3 hours, and 3 parts of nano-silicon dioxide (particle size of 30 nm) were dried for 2.5 hours at a drying temperature of 135°C;
[0023] Step 2: Prepolymer synthesis: under nitrogen protection, add 45 parts of dehydrated polytetramethylene glycol, 20 parts of polybutylene adipate glycol, 25 parts of diphenylmethane diisocyanate and 10 parts of toluene diisocyanate into a reaction kettle, control the temperature at 60°C, and stir the reaction for 1.5 hours;
[0024] Step 3: Chain extension reaction: Add 5 parts of 1,4-butanediol, 4 parts of ethylene glycol and 0.8 parts of ultraviolet absorber to the prepolymer, continue stirring and heat to 80°C, and react for 2.5 hours;
[0025] Step 4: Filler dispersion: Slowly add 3 parts of dried nano-silicon dioxide into the reaction system and disperse it under high-speed stirring (1000 rpm) for 50 minutes;
[0026] Step 5: Molding treatment: Pour the reacted composite material into a mold, cure it at 110°C for 3 hours, and then place it at room temperature for 40 hours.
[0027] The composition prepared in this example is a solid polyurethane composite product, which can be used in new energy vehicle parts and components such as battery housings, bumpers, etc., meeting the requirements in terms of strength, toughness, weather resistance, etc.
[0028] The molecular weight mentioned above refers to the relative molecular mass.
[0029] The antioxidant mentioned above is a material with the chemical name of 2,6-di-tert-butyl-4-methylphenol;
[0030] The ultraviolet absorber mentioned above adopts a material with the chemical name of 2-hydroxy-4-methoxybenzophenone.
[0031] Example 2
[0032] In this embodiment, the content of each extract is adjusted on the basis of the embodiment 1, as follows:
[0033] 50 parts of polytetramethylene glycol, 25 parts of polybutylene adipate glycol, 28 parts of diphenylmethane diisocyanate, 12 parts of toluene diisocyanate, 6 parts of 1,4-butanediol, 5 parts of ethylene glycol, 4 parts of nano-silicon dioxide, 1.5 parts of antioxidant, and 1 part of ultraviolet absorber.
[0034] Example 3
[0035] In this embodiment, the content of each extract is adjusted on the basis of the embodiment 1, as follows:
[0036] 40 parts of polytetramethylene glycol, 18 parts of polybutylene adipate glycol, 22 parts of diphenylmethane diisocyanate, 8 parts of toluene diisocyanate, 4 parts of 1,4-butanediol, 3 parts of ethylene glycol, 2 parts of nano-silica, 1 part of antioxidant, and 0.6 parts of ultraviolet absorber.
[0037] Example 4
[0038] In this embodiment, the content of each extract is adjusted on the basis of the embodiment 1, as follows:
[0039] 40 parts of polytetramethylene glycol, 18 parts of polybutylene adipate glycol, 22 parts of diphenylmethane diisocyanate, 8 parts of toluene diisocyanate, 4 parts of 1,4-butanediol, 3 parts of ethylene glycol, 2 parts of nano-silica, 1 part of antioxidant, and 0.6 parts of ultraviolet absorber.
[0040] Example 5
[0041] In this embodiment, the content of each extract is adjusted on the basis of the embodiment 1, as follows:
[0042] 55 parts of polytetramethylene glycol, 22 parts of polybutylene adipate glycol, 20 parts of diphenylmethane diisocyanate, 15 parts of toluene diisocyanate, 5.5 parts of 1,4-butanediol, 4.5 parts of ethylene glycol, 3.5 parts of nano-silicon dioxide, 1.8 parts of antioxidant, and 1.2 parts of ultraviolet absorber.
[0043] Example 6
[0044] In this embodiment, the content of each extract is adjusted on the basis of the embodiment 1, as follows:
[0045] 60 parts of polytetramethylene glycol, 30 parts of polybutylene adipate glycol, 35 parts of diphenylmethane diisocyanate, 15 parts of toluene diisocyanate, 8 parts of 1,4-butanediol, 6 parts of ethylene glycol, 5 parts of nano-silicon dioxide, 2 parts of antioxidant, and 1.5 parts of ultraviolet absorber.
[0046] Comparative Example 1
[0047] In this comparative example, the content of each extract is adjusted on the basis of Example 1, as follows:
[0048] 65 parts of polytetramethylene glycol, 8 parts of polybutylene adipate glycol, 12 parts of diphenylmethane diisocyanate, 3 parts of toluene diisocyanate, 2 parts of 1,4-butanediol, 1 part of ethylene glycol, 0.5 parts of nano-silica, 0.2 parts of antioxidant, and 0.1 parts of ultraviolet absorber.
[0049] Comparative Example 2
[0050] In this comparative example, the content of each extract is adjusted on the basis of Example 1, as follows:
[0051] 25 parts of polytetramethylene glycol, 35 parts of polybutylene adipate glycol, 40 parts of diphenylmethane diisocyanate, 18 parts of toluene diisocyanate, 9 parts of 1,4-butanediol, 7 parts of ethylene glycol, 6 parts of nano-silicon dioxide, 2.5 parts of antioxidant, and 2 parts of ultraviolet absorber.
[0052] Comparative Example 3
[0053] In this comparative example, the content of each extract is adjusted on the basis of Example 1, as follows:
[0054] 45 parts of polytetramethylene glycol, 20 parts of polybutylene adipate glycol, 25 parts of diphenylmethane diisocyanate, 10 parts of toluene diisocyanate, 5 parts of 1,4-butanediol, 4 parts of ethylene glycol, 1.2 parts of antioxidant, and 0.8 parts of ultraviolet absorber.
[0055] Comparative Example 4
[0056] In this comparative example, the content of each extract is adjusted on the basis of Example 1, as follows:
[0057] 45 parts of polytetramethylene glycol, 20 parts of polybutylene adipate glycol, 25 parts of diphenylmethane diisocyanate, 10 parts of toluene diisocyanate, 5 parts of 1,4-butanediol, 4 parts of ethylene glycol, 3 parts of nano-silicon dioxide, and 0.8 parts of ultraviolet absorber.
[0058] Comparative Example 5
[0059] In this comparative example, the content of each extract is adjusted on the basis of Example 1, as follows:
[0060] 45 parts of polytetramethylene glycol, 20 parts of polybutylene adipate glycol, 25 parts of diphenylmethane diisocyanate, 10 parts of toluene diisocyanate, 5 parts of 1,4-butanediol, 4 parts of ethylene glycol, 3 parts of nano-silicon dioxide, and 1.2 parts of antioxidant.
[0061] Comparative Example 6
[0062] In this comparative example, the content of each extract is adjusted on the basis of Example 1, as follows:
[0063] 70 parts of polytetramethylene glycol, 5 parts of polybutylene adipate glycol, 15 parts of diphenylmethane diisocyanate, 5 parts of toluene diisocyanate, 3 parts of 1,4-butanediol, 2 parts of ethylene glycol, 1 part of nano silicon dioxide, 0.5 parts of antioxidant, and 0.3 parts of ultraviolet absorber.
[0064] Comparative Example 7
[0065] In this comparative example, the content of each extract is adjusted on the basis of Example 1, as follows:
[0066] 10 parts of polytetramethylene glycol, 50 parts of polybutylene adipate glycol, 20 parts of diphenylmethane diisocyanate, 10 parts of toluene diisocyanate, 6 parts of 1,4-butanediol, 4 parts of ethylene glycol, 3 parts of nano-silicon dioxide, 1.5 parts of antioxidant, and 1 part of ultraviolet absorber.
[0067] The compositions of the present invention in the example groups and the compositions of the present invention in the comparative examples were subjected to the following tests:
[0068] Shore Hardness Test: Measures the hardness of a material;
[0069] Tensile strength test: measure the tensile strength and elongation at break of materials;
[0070] Thermal performance test: Place the material sample in a heat deformation temperature tester and heat the sample at a certain heating rate under a certain load. During the test, regularly test the changes in its mechanical properties (such as tensile strength retention) to evaluate the heat resistance of the material;
[0071] Weathering test: Use a UV aging test chamber, place the material sample in the test chamber, and set the appropriate UV wavelength, irradiation intensity and test cycle. During the test, regularly test the changes in its mechanical properties (such as tensile strength retention rate) to evaluate the material's UV aging resistance;
[0072] The specific test results of the composite materials made of the compositions of the present invention in each embodiment and comparative example are shown in the following table:
[0073]
[0074] Comparison of the performance test results in Examples 1-6 and Comparative Examples 1-7 shows that the polyurethane composite products prepared in Examples 1-6 have excellent overall performance in terms of tensile strength, flexural strength, impact toughness and weather resistance, and all performance indicators can well meet the use requirements of new energy vehicle parts such as battery housings, bumpers, etc. However, in Comparative Examples 1-7, due to the deviation of the content of each component from the reasonable range or abnormal factors such as molecular weight, the performance of the material products deteriorated to varying degrees. For example, the content of each component in Comparative Example 1 is low, and its various performance indicators are significantly lower than those in the embodiment, and the performance standards of new energy vehicle accessories cannot be reached; the molecular weight of polytetrahydrofuran ether diol and polybutylene adipate diol in Comparative Example 2 is abnormal, which has a negative impact on the comprehensive performance of the material, especially the significant decline in weather resistance; Comparative Example 3 does not add nano silicon dioxide, and the strength and toughness of the material are affected; Comparative Example 4 does not add antioxidants, and the weather resistance and long-term stability deteriorate; Comparative Example 5 does not add ultraviolet absorber, and the strength retention rate is low in the light aging test; Comparative Example 6 polytetrahydrofuran ether diol content is too high and polybutylene adipate diol content is too low, resulting in an imbalance in material performance; Comparative Example 7 polytetrahydrofuran ether diol content is too low and polybutylene adipate diol content is too high, which also makes the comprehensive performance of the material unable to meet the requirements. Through the comparative test of the embodiment and the comparative example, it is possible to determine the reasonable content range of each component and the important influence of related factors (such as additive types, etc.) on the performance of polyurethane composite products, which provides strong data support for optimizing material formulations to better apply to new energy vehicle parts components.
[0075] The polyurethane composite material of the present invention can show good comprehensive performance under specific formula and preparation process. For the parts of the battery shell of the new energy vehicle, because the battery shell needs a certain strength to protect the battery, and at the same time, it must have good toughness to prevent collision damage during vehicle driving, and in the long-term outdoor use environment, heat resistance and UV resistance can ensure its service life, the ratio of each component in Example 1 is more suitable for making a battery shell, for the bumper of the new energy vehicle, the bumper needs a higher strength to resist collision, good toughness (high elongation at break) to absorb collision energy, and in the outdoor environment, excellent heat resistance and UV resistance can reduce the risk of aging and damage, and the ratio of each component in Example 2 is more suitable for making a bumper, and for some non-critical appearance parts of the new energy vehicle, such as body decorative strips, etc. These parts do not have particularly high strength requirements, but require a certain toughness to adapt to the vibration and slight collision during vehicle driving, and at the same time, its heat resistance and UV resistance can ensure the durability of the appearance, and the ratio of each component in Example 5 is more suitable for making non-critical appearance parts, so the requirements of new energy vehicle accessories components in different parts can be met by changing the ratio of each component.
[0076] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A polyurethane composite material used in new energy automobile parts components, characterized in that: The composition comprises, by weight, 30-60 parts of polytetramethylene glycol, 10-30 parts of polybutylene adipate glycol, 15-35 parts of diphenylmethane diisocyanate, 5-15 parts of toluene diisocyanate, 3-8 parts of 1,4-butanediol, 2-6 parts of ethylene glycol, 1-5 parts of nano silicon dioxide, 0.5-2 parts of antioxidant and 0.3-1.5 parts of ultraviolet absorber.
2. The polyurethane composite material for new energy automobile parts according to claim 1, characterized in that: The polyurethane composite material used for new energy vehicle parts components includes, by weight: 40-50 parts of polytetramethylene ether glycol, 15-25 parts of polybutylene adipate glycol, 20-30 parts of diphenylmethane diisocyanate, 7-13 parts of toluene diisocyanate, 4-7 parts of 1,4-butanediol, 3-5 parts of ethylene glycol, 2-4 parts of nano silicon dioxide, 1-1.5 parts of antioxidant, and 0.8-1.2 parts of ultraviolet absorber.
3. The polyurethane composite material for new energy automobile parts according to claim 1, characterized in that: The polyurethane composite material used for new energy vehicle parts components includes, by weight: 50 parts of polytetramethylene ether glycol, 25 parts of polybutylene adipate glycol, 28 parts of diphenylmethane diisocyanate, 12 parts of toluene diisocyanate, 6 parts of 1,4-butanediol, 5 parts of ethylene glycol, 4 parts of nano-silica, 1.5 parts of antioxidant, and 1 part of ultraviolet absorber.
4. The polyurethane composite material for new energy automobile parts according to claim 1, characterized in that: The molecular weight of the polytetramethylene ether diol is 3000-4000, and the molecular weight of the polybutylene adipate diol is 1500-2500.
5. The polyurethane composite material for new energy automobile parts according to claim 1, characterized in that: The particle size of the nano silicon dioxide is 10-50nm.
6. A method for preparing the polyurethane composite material used for new energy automobile parts components according to any one of claims 1 to 3, characterized in that: The specific steps are as follows: Step 1: Raw material pretreatment: polytetrahydrofuran ether glycol, polybutylene adipate glycol, 1,4-butanediol, ethylene glycol and antioxidant are vacuum dehydrated for 2-4 hours, and nano-silica is dried for 2-3 hours; Step 2: Prepolymer synthesis: under nitrogen protection, add dehydrated polytetramethylene glycol, polybutylene adipate glycol, diphenylmethane diisocyanate and toluene diisocyanate into a reaction kettle, control the temperature at 50-70°C, and stir the reaction for 1-2h; Step 3: Chain extension reaction: Add 1,4-butanediol, ethylene glycol and UV absorber to the prepolymer, continue stirring and heat to 70-90°C, and react for 2-3 hours; Step 4: Filler dispersion: Slowly add the dried nano-silica into the reaction system and disperse it for 30-60 minutes under high-speed stirring (800-1200 rpm); Step 5: Molding treatment: Pour the reacted composite material into a mold, cure it at 100-120°C for 2-4 hours, and then place it at room temperature for 24-48 hours.
7. The method for preparing the polyurethane composite material used for new energy automobile parts assembly according to claim 6, characterized in that: In the step 1, the vacuum dehydration temperature is 85-95°C, and the drying temperature of the nano-silicon dioxide is 130-140°C.
Citation Information
Patent Citations
Composite enhanced hydrolysis-resistant thermoplastic polyurethane elastomer and its preparation method
CN103897380A
Thermoplastic elastomer composition, thermoplastic elastomer, and method for producing thermoplastic elastomer
WO2016114243A1